Assessment of Length, External Outer Diameter and Positional Variations in Normal and Inflamed Appendix (Medical Forum Monthly, 2020)
Objective: To assess the length, external outer diameter and positional variations in normal and inflamed appendix among the adult population of Rawalpindi operated for acute appendicitis.Study Design: Cross sectionalPlace and Duration of Study: This study was conducted at the Department of Surgery and histopathology of Benazir Bhutto Hospital. Two years (Jan 2018 to Feb 2020).Materials and Methods: Two hundred patients operated for acute appendicitis were included in the study. Out of these, patients confirmed on gross examination and histopathology were classed as true cases. Length and external outer diameter were calculated for both inflamed and non-inflamed appendices. Mean length and external out diameter was compared in both the groups. Positional variations were also noted for all the appendices removed may they be inflamed or not inflamed.Results: Out of 200 patients operated with clinical suspicion of acute appendicitis, 179 (89.5%) showed the presence of inflammation on gross and histopathology while 21 (10.5%) had non-inflamed appendix. Mean age of the study participants was 30.6±2.17 years. Mean length of the appendix in cases with confirmed inflammation was 08.37 ± 3.4 cm while without inflammation was 6.72 ± 3.1cm (p-value<0.01). Mean external outer diameter of the appendix in cases with confirmed inflammation was 4.22 ± 2.1mm while without inflammation was 3.37 ± 1.4 mm (p-value<0.01). Most common type of location in both the groups was retrocecal.Conclusion: Inflammation may pose a direct effect on length and diameter of the appendix as there was a significant increased length and diameter recorded in patients with confirmed inflammation as compared to those without any inflammation. Position of appendix was almost same in both the groups.